Effect of curing method on compressive strength of rapid hardening sulphoaluminate cement mortar at -10 °C. Issue 1 (June 2021) - Wang, Zhihang; Bai, Erlei; Wang, Han; Meng, Xin; Luo, Xin; Huang, He
Abstract: Rapid hardening sulphoaluminate cement has been widely studied and applied under low temperature, normal temperature and high temperature conditions, but the research under negative temperature conditions has just started. Through three curing methods: constant negative temperature curing, negative temperature changing positive temperature curing, and pre-curing, the influence of different curing methods on the compressive strength of rapid hardening sulphoaluminate cement mortar at -10 °C is discussed. The results show that pre-curing measures can significantly improve the early compressive strength of rapid hardening sulphoaluminate cement mortar. The longer the pre-curing time, the greater the compressive strength. Under the condition of -10 °C, the rapid hardening sulphoaluminate cement can still be continuously hydrated, and the hydration products remain unchanged.